2015
DOI: 10.1093/cercor/bhu316
|View full text |Cite
|
Sign up to set email alerts
|

Topologically Reorganized Connectivity Architecture of Default-Mode, Executive-Control, and Salience Networks across Working Memory Task Loads

Abstract: The human brain is topologically organized into a set of spatially distributed, functionally specific networks. Of these networks, the default-mode network (DMN), executive-control network (ECN), and salience network (SN) have received the most attention recently for their vital roles in cognitive functions. However, very little is known about whether and how the interactions within and between these 3 networks would be modulated by cognitive demands. Here, we employed graph-based modularity analysis to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
188
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 55 publications
25
188
3
Order By: Relevance
“…Although most studies examining connectivity during motorrelated tasks focus on within-network organization (Biswal et al, 1995;Jiang et al, 2004;Rissman et al, 2004;Sun et al, 2004Sun et al, , 2007Zhuang et al, 2005;Bardouille and Boe, 2012), many studies probing working memory focus on internetwork integration. Our findings are consistent with previous studies demonstrating increased integration during tasks presumed to tap working memory with increasing load or compared to rest (Kitzbichler et al, 2011;Gordon et al, 2012;Cohen et al, 2014;Liang et al, 2016) and that increased integration is related to increased behavioral performance (Bassett et al, 2009;Cohen et al, 2014;Stanley et al, 2014;Braun et al, 2015). We extend this literature by using several measures of segregation and integration to provide convergent evidence for increased integration during working memory.…”
Section: Discussionsupporting
confidence: 92%
“…Although most studies examining connectivity during motorrelated tasks focus on within-network organization (Biswal et al, 1995;Jiang et al, 2004;Rissman et al, 2004;Sun et al, 2004Sun et al, , 2007Zhuang et al, 2005;Bardouille and Boe, 2012), many studies probing working memory focus on internetwork integration. Our findings are consistent with previous studies demonstrating increased integration during tasks presumed to tap working memory with increasing load or compared to rest (Kitzbichler et al, 2011;Gordon et al, 2012;Cohen et al, 2014;Liang et al, 2016) and that increased integration is related to increased behavioral performance (Bassett et al, 2009;Cohen et al, 2014;Stanley et al, 2014;Braun et al, 2015). We extend this literature by using several measures of segregation and integration to provide convergent evidence for increased integration during working memory.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between DMN, salience and ECNs is under investigation, but recent studies defined that DMN and salience work oppositely, meaning that the increase of the first is followed by a decrease in the second, and vice‐versa [Balthazar, et al, 2014]. Some authors suggest that this mechanism involves a mediation of activity executed by the salience network guiding the focus on internal (DMN) or external (ECN) process and stimulus [Liang et al, 2016]. …”
Section: Discussionmentioning
confidence: 99%
“…The rotational displacements were converted from radians to millimeters by calculating the displacement on the surface of a sphere of radius 50 mm Liang et al, 2013). To moderate the effects of head motion on estimates of functional connectivity, we censored volumes within each participant's restingstate fMRI time series that were associated with sudden head motion (i.e., the volumes with FD i ÏŸ0.5 mm).…”
Section: <0001mentioning
confidence: 99%
“…Resting-state fMRI studies have demonstrated that hubs in the brain, which have high functional connectivity strength (FCS) and high rates of cerebral blood flow and glucose metabolism (Liang et al, 2013;Tomasi et al, 2013), serve to integrate diverse information sources (Achard et al, 2006;Buckner et al, 2009;Bullmore and Sporns, 2009;He and Evans, 2010;van den Heuvel and Sporns, 2013). These brain hubs are predominantly located in regions of the default mode network (DMN), including the posterior cingulate cortex (PCC)/precuneus (PCU), the medial prefrontal cortex, and the lateral temporal and parietal cortices (Raichle et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation